Optimisation of small arms defeat via dynamic jacket removal - Roberts, A. (Cranfield University, 2017)
The majorities of studies into penetration by small arms have neglected the contribution of the jacket to the penetration event due to its small mass compared to the rest of the bullet. Recent research has suggested that the jacket does actually play a measurable role in the penetration of a target. This project has focused on the concept of dynamic jacket removal as an approach to optimise small arms defeat. This approach was envisaged to address the gap in current knowledge with regards to the role of the bullet jacket in the penetration of a target. Here, jacket stripping techniques were employed, elucidating underling mechanisms where armour piercing (AP) rounds were fired at target materials. Forward ballistic experiments were conducted, utilising conventional ballistic testing on an indoor small arms range as well as 30 mm and 50 mm smooth bore single stage light gas guns. To compliment this work, reverse ballistic experimentation was also undertaken on a 50 mm single stage light gas gun. Impact events were interrogated via a series of diagnostics including high speed video imaging, flash X ray radiography and depth of penetration testing. Experimental results were complimentary, providing insight into two key competing effects with regards to the jacket on penetration. These were the potential for the jacket to cushion / damp the impact, as well as the physical confinement resulting from the presence of the jacket itself around the bullet core. Further, these experiments also identified a potential optimum in terms of stripping plate design. In addition, to further investigate the role of the bullet jacket, sample cores and jacket materials were loaded both together and in isolation using a split Hopkinson pressure bar, with results in particular highlighting the cushioning effect of the jacket material. Limited numerical simulations were also produced using Ansys® Autodyn. These numerical results further elucidated the experimental work – again highlighting the importance of the jacket in terms of cushioning the impact event / reducing the subsequent pre-loading of the penetrating AP core. Overall, both experimental and numerical results showed that the bullet jacket does indeed aid in penetration. In corollary, in practical terms, jacket removal has the potential to aid in armour performance – with the experiments conducted herein providing insight into dynamic jacket removal. In terms of such stripping mechanisms, it was demonstrated that a plate thickness comparable to the calibre of the bullet appeared optimal. Further, results have also shown the importance of hardness and other material properties when considering the final defeat of an incident projectile through spallation.